The Influence of Product Quality, Price Perception, Brand Image, and Promotion on Purchase Decisions for Samsung Televisions in Jakarta - Yodi Listianto; Aditya Burhan (Economics and Digital Business Review, 2026)
This research examines the influence of product quality, price perception, brand image, and promotion on consumers’ purchasing decisions regarding Samsung televisions in Jakarta. The study adopts a quantitative research design utilizing a survey approach. Data were gathered from 100 respondents who had previously purchased Samsung televisions and were selected through purposive sampling. The collected data were analyzed using multiple linear regression analysis, partial significance testing (t-test), simultaneous significance testing (F-test), and the coefficient of determination (R²). The results indicate that product quality, brand image, and promotion significantly and positively affect purchasing decisions. In contrast, price perception does not demonstrate a significant impact on consumers’ purchasing decisions. Among the independent variables examined, promotion emerged as the strongest determinant of purchasing decisions. Furthermore, the findings of the simultaneous test confirm that product quality, price perception, brand image, and promotion collectively exert a significant influence on purchasing decisions. The coefficient of determination value (R² = 0.628) suggests that 62.8% of the variation in purchasing decisions can be explained by the variables included in the model, while the remaining 37.2% is attributable to other factors not investigated in this study. These findings highlight the importance of maintaining product quality, strengthening brand image, and implementing effective promotional strategies to encourage consumer purchasing behavior.